Decoupling in India's building construction sector: trends, technologies and policies. Issue 1 (2nd January 2019) - Gokarakonda, Sriraj; Shrestha, Shritu; Caleb, Pratibha Ruth; Rathi, Vaibhav; Jain, Rohan; Thomas, Stefan; Topp, Kilian; Niazi, Zeenat
ABSTRACT: India's present development trajectory is at a crucial juncture with a requirement to meet the demands of a population of over 1.2 billion while ensuring environmental sustainability. The resulting economic growth over the past two decades has over-exploited finite natural resources and led to tremendous environmental degradation. Therefore, decoupling economic growth from resource consumption is crucial in the transformation towards a green economy. Building construction is one of the most resource-intensive sectors, as well as creating a high impact on the environment. This study analyzes existing mechanisms in India's building construction sector that attempt to decouple economic growth from resource use and environmental impacts. The key contributors for decoupling are analyzed. Recommendations for regulations, market incentives, transparency, data monitoring and capacity-building are provided for an array of policy initiatives targeted at political and financial decision-makers at the national, state and local levels for different buildings.